Concepts of persistent weakening or loss of function of one of the senses or organs in the Turkish Penal Code: Systematic Review - Çelik, Cemil; Ata, Uğur (The Bulletin of Legal Medicine, 2022)
As a result of persistent weakening or loss of function of one of the senses or organs, which are stated in the Turkish Penal Code, penalty increases are applied at varying rates depending on whether the act was committed by negligence, willful or torture. The need for a separate guide has become more evident today, as there are deficiencies in the guide used for the evaluation of these situations, and the existing debates about the charts used to determine the financial compensation recommended to be used to support the guide. Considering the problems in practice, a separate guide is needed for the evaluation of sensory and organ function, which can be considered as a second-line forensic medical evaluation. Since the definition of organ is evaluated differently in the Turkish Penal Code and in the medical literature, first of all, it will be important to ensure a common language unity in practice, to define all the body parts that will be included in the concept of organ in forensic medicine practices. Including studies in the literature in the guide will provide a more reassuring approach in updating the guide. What are the concepts of organs and senses from a forensic medicine perspective? What should be considered in the forensic medical examination in the evaluation of their functions? Concepts of permanent weakening/loss of the function of the senses or organs will be discussed in terms of legal and forensic medicine and solutions will be discussed by revealing the problems experienced in practice.